Level of men’s involvement in spousal contraceptive use among married men in a local government, Nigeria - Ilori, Oluwatosin Ruth; Ogedengbe, Stella; Awodutire, Phillip Oluwatobi (Acta Scientiarum. Health Sciences, 2023)
Engaging men in family planning programs holds promise as a means to improve access and use of family planning in Nigeria. A growing number of programmatic examples and research findings in the region, as well as global evidence, demonstrate the benefits of male engagement. The aim of this study is to determine spousal involvement in issues pertaining to family planning usage by their wives. The community based study was carried out among married men in Akure South Local Government in Ondo state between May 2021 and August 2021 using a multistaged sampling method. One hundred and ninety-six men were sampled using a semi structured questionnaire developed by the author from previous similar studies with the aid of research assistants. Data was analyzed using SPSS version 22. Frequency tables were drawn and chi square used to test for association between respondents’ socio demographic characteristics and their support for contraception, p value was set at <0.05. One hundred and seventy-two (90.5%) respondents have heard about contraceptives before, health personnel being the commonest source of income. Condom happened to be known by 133 (71.9%) respondents. Fifty (28.7%) respondents have good spousal involvement in contraception while 124 (71.3%) are poorly involved. The perceived reason why men do not support their wives in issues that pertain to family planning is because contraceptives are assumed to be women affair (101,55.5%). Also, the irreversible nature of family planning commodities was identified by 55, 30.6% respondents. Occupation and estimated monthly income of respondents were statistically significant with spousal involvement with a p value of 0.030 and 0.012 respectively. Spousal support for family planning was poor in this study. More enlightenment and education is recommended to be offered to men in order to increase the uptake of family planning among women of reproductive age group.